2011
DOI: 10.1152/ajprenal.00065.2010
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating effect of angiotensin-(1–7) on angiotensin II-mediated NAD(P)H oxidase activation in type 2 diabetic nephropathy of KK-Ay/Ta mice

Abstract: -7) is associated with vasodilation and nitric oxide synthase stimulation. However, the role of ANG-(1-7) in type 2 diabetes mellitus is unknown. In this study, we examined the hypothesis that ANG-(1-7) attenuates ANG II-induced reactive oxygen species stress (ROS)-mediated injury in type 2 diabetic nephropathy of KK-A y /Ta mice. KK-A y /Ta mice were divided into four groups: 1) a control group; 2) ANG II infusion group; 3) ANG IIϩANG-(1-7) coinfusion group; and 4) ANG IIϩANG-(1-7)ϩD-Ala 7 -ANG-(1-7) (A779) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 43 publications
4
71
0
Order By: Relevance
“…Mas knockout mice lack the antidiuretic action of Ang(1-7) (Santos and Baracho, 1992). Both the anti-and proinflammatory effects of Ang (1)(2)(3)(4)(5)(6)(7) were reported in kidney of Mas knockout mice (Esteban et al, 2009;Singh et al, 2010b;Moon et al, 2011;Bernardi et al, 2012;Giani et al, 2012;Harris, 2012;Chou et al, 2013;Santos et al, 2013).…”
Section: G Pathophysiological Evidence Of Mas Receptor Interaction Wmentioning
confidence: 99%
“…Mas knockout mice lack the antidiuretic action of Ang(1-7) (Santos and Baracho, 1992). Both the anti-and proinflammatory effects of Ang (1)(2)(3)(4)(5)(6)(7) were reported in kidney of Mas knockout mice (Esteban et al, 2009;Singh et al, 2010b;Moon et al, 2011;Bernardi et al, 2012;Giani et al, 2012;Harris, 2012;Chou et al, 2013;Santos et al, 2013).…”
Section: G Pathophysiological Evidence Of Mas Receptor Interaction Wmentioning
confidence: 99%
“…Measurement of NF-B activation. Nuclear extracts were obtained from renal cortices using a Nuclear Extract Kit (Active Motif, Tokyo, Japan) as previously described (20,35). NF-B activation was measured using an NF-B Transcription Factor Assay Kit (Active Motif) according to the manufacturer's recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…Besides its physiological relevance for kidney homeostasis, the ACE2/Ang-(1-7)/Mas axis also has an important and controversial role in renal diseases, acting as a renoprotective (Oudit et al 2006, 2010, Soler et al 2007, Pinheiro et al 2009, Burns et al 2010, Dilauro et al 2010, Zhang et al 2010, Giani et al 2011, Liu et al 2011b, Moon et al 2011, Stegbauer et al 2011, Zhong et al 2011, Barroso et al 2012, Kim et al 2012, Nadarajah et al 2012 or a proinflammatory (Esteban et al 2009, Velkoska et al 2011 agent. Briefly, Pinheiro et al (2009) reported that mice with genetic deletion of Mas developed renal dysfunction with an increase of glomerular tuft diameter and enhancement of fibronectin and collagen IV and III deposition, besides an increase of AT 1 and TGF-b expression.…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%